Pengeboran Air Di Dusun Asemberit Kabupaten Sampang Madura Dengan Menggunakan Metode Geolistrik Admt (Fakultas Teknik, Universitas Brawijaya, 2023)
The need for clean water is increasing over time so that the problem of providing clean water is currently a special concern because it fulfills the basic needs of human life. The benefits of clean water include filling fluids in the body, helping with daily activities, agricultural irrigation, and maintaining the environmental ecosystem. Some of the problems that arise as a result of water shortages of poor quality are public health problems and decreased agricultural productivity due to low soil fertility levels. One factor is the type of underground water source (ABT). In areas that have coastal and coastal morphology, this will greatly influence the quality of ABT. This results in surface and ground water conditions with high salinity or are brackish to salty. Apart from that, with the characteristics of coastal and coastal areas, facts on the ground show that the water produced has high levels of alkali and lime. One area with soil characteristics as described is the island of Madura, especially in the Sampang Regency area. Empirical measurement results show that drilling to obtain clean water is located at 40-60 meters deep.